Analisis SWOT Peran Dinas ESDM Provinsi Bengkulu dalam Pengelolaan Berkelanjutan Pertambangan Batuan - Didi Ardiyansyah; Radeni Ilyan Putra; Risna Armalia; Reflis Reflis; Satria P Utama (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the strategic role of the Energy and Mineral Resources Office (DESDM) of Bengkulu Province in managing stone mining activities sustainably. Sustainable mining management must not only focus on economic gains and increasing regional revenue (PAD), but also on environmental preservation and the welfare of local communities. The research employs a qualitative descriptive method with a SWOT analysis approach to identify internal strengths and weaknesses, as well as external opportunities and threats. Data were collected through in-depth interviews with relevant stakeholders and analysis of official documents from DESDM. The results indicate that DESDM’s key strengths include strong legal frameworks and leadership support. However, weaknesses are evident in limited regional regulations, suboptimal cross-sector coordination, and underutilization of digital technologies. Opportunities include the advancement of information technology, support from stakeholders, and potential PAD growth. Meanwhile, threats arise from dynamic regulatory changes and unequal competency levels among mining operators. An aggressive strategy is recommended, focusing on leveraging internal strengths to capture external opportunities through capacity-building programs, regulatory reforms, cross-sector collaboration, and digital supervision systems. This research provides a basis for formulating more adaptive, participatory, and sustainable policies for regional natural resource governance, with the goal of balancing environmental conservation and economic development.